2009
DOI: 10.1002/adfm.200900399
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Emulsions as the Basis of Biological Sensors for the Optical Detection of Bacteria and Viruses

Abstract: A versatile sensing method based on monodisperse liquid crystal (LC) emulsion droplets detects and distinguishes between different types of bacteria (Gram +ve and −ve) and viruses (enveloped and non‐enveloped). LCs of 4‐cyano‐4'‐pentylbiphenyl transition from a bipolar to radial configuration when in contact with Gram −ve bacteria (E. coli) and lipid‐enveloped viruses (A/NWS/Tokyo/67). This transition is consistent with the transfer of lipid from the organisms to the interfaces of the micrometer‐sized LC dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
231
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(243 citation statements)
references
References 35 publications
1
231
2
2
Order By: Relevance
“…This stabilizes the interface and prevents shell rupture, but, owing to the disordered polymer chain, it does not necessarily have a strong impact on the LC alignment. The resulting planar alignment is instead probably a result of the contact with the polar water phase, which is known to induce planar alignment [20]. The Pluronics F-127 surfactant has turned out to be compatible with planar as well as homeotropic alignment, and we found opposite results for nematic and smectic phases [19].…”
Section: Introductionmentioning
confidence: 55%
“…This stabilizes the interface and prevents shell rupture, but, owing to the disordered polymer chain, it does not necessarily have a strong impact on the LC alignment. The resulting planar alignment is instead probably a result of the contact with the polar water phase, which is known to induce planar alignment [20]. The Pluronics F-127 surfactant has turned out to be compatible with planar as well as homeotropic alignment, and we found opposite results for nematic and smectic phases [19].…”
Section: Introductionmentioning
confidence: 55%
“…The liquid crystal amplifies the binding event such that it becomes easily visible on a microscopic scale. The concept is most often applied to planar liquid crystal samples but also liquid crystal droplets were successfully used for detecting bacteria and viruses [309]. While most biodetectors require fluorescent tagging or labeling of key molecules, this is unnecessary with the liquid crystal-based detection technique.…”
Section: Biodetection With Liquid Crystalsmentioning
confidence: 99%
“…It was demonstrated that LC sensors are capable of determining chemicals that can be present as gases [1], identifying biological molecules (proteins, oligopeptides, immunoglobulins and nucleic acids) [2,3,4] sensing low concentrations of surfactants, lipids and charged molecules [5,6], single and double stranded DNA fragments on solid surfaces [7]. LC sensors were used for identification of viruses, bacteria and mammalian cells [8,9] and so on.…”
Section: Introductionmentioning
confidence: 99%